Knowledge and self-confidence of antibiotic resistance, appropriate antibiotic therapy, and antibiotic stewardship among pharmacy undergraduate students in three Asian countries - Abubakar, Usman; Syed Sulaiman, Syed Azhar; Muhammad, Haseeb T; Ramatillah, Diana Laila; Amir, Omalhassan (Elsevier Inc., 2020)
Background and purpose: Training pharmacy students in infectious diseases (ID) is important to enable them to participate in antibiotic stewardship programs. This study evaluated knowledge and self-confidence regarding antibiotic resistance, appropriate antibiotic therapy, and antibiotic stewardship among final year pharmacy undergraduate students.